Cambios esqueléticos, faciales y dentoalveolares producidos por el tratamiento con placas de acetato y elásticos de clase III en pacientes con mesiorrelación esquelética y dental en dentición decidua o mixta temprana (2011)
ABSTRACT: The purpose of this study was to establish the clinical and radiographic changes produced by using bimaxillary acetate plates with Class III elastics during one year for treatment of skeletal Class III in patients with early deciduous or mixed dentition. Methods: a quasi-experimental prospective clinical study was carried out in 26 subjects, ages three to nine years. Lateral cephalometric radiographs and study models were taken at the beginning, six months, and one year of treatment; post-treatment changes were evaluated after three years in five subjects. During the statistical analysis descriptive measures were obtained, and the Anova test for repeated measures was used to determine changes over time; also, the nonparametric Wilcoxon test was used with a significance level of 0.005. Results: favorable skeletal changes were achieved in the mandible, especially at the SNB, facial and gonial angles, the pog distance perpendicular to N, the lower anterior facial height, and the Y axis; dentoalveolarly, there were improvements in both horizontal overbite and Witts, as well as in facial aesthetics, as evidenced by the decrease of the E-plane FH angle and lower lip protrusion. After three years of treatment, stability of the results was observed. Conclusions: acetate plates with Class III elastics demonstrated to be a stable and effective therapy, according to evaluation three years after treatment, for facial improvement of skeletal Class III with anterior crossbite in early primary or mixed dentition.